2017
DOI: 10.1186/s12943-017-0629-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived CXCL5 promotes human colorectal cancer metastasis through activation of the ERK/Elk-1/Snail and AKT/GSK3β/β-catenin pathways

Abstract: BackgroundMetastasis is a major cause of death in human colorectal cancer patients. However, the contribution of chemokines in the tumor microenvironment to tumor metastasis is not fully understood.MethodsHerein, we examinined several chemokines in colorectal cancer patients using chemokine ELISA array. Immunohistochemistry was used to detect expression of CXCL5 in colorectal cancer patients tissues. Human HCT116 and SW480 cell lines stably transfected with CXCL5, shCXCL5 and shCXCR2 lentivirus plasmids were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
187
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(191 citation statements)
references
References 39 publications
2
187
1
1
Order By: Relevance
“…[33][34][35] ERK is an important factor for regulating proliferation, apoptosis, migration and invasion through various signalling in CRC cells. [36][37][38][39] Our findings demonstrated that overexpression of SPNS2 increased Akt and ERK phosphorylation and SPNS2-induced malignant behaviours were abolished by Akt or ERK inhibitor, suggesting that SPNS2 may regulate the malignancy of CRC cells by activating Akt and ERK signalling.…”
Section: Discussionmentioning
confidence: 54%
“…[33][34][35] ERK is an important factor for regulating proliferation, apoptosis, migration and invasion through various signalling in CRC cells. [36][37][38][39] Our findings demonstrated that overexpression of SPNS2 increased Akt and ERK phosphorylation and SPNS2-induced malignant behaviours were abolished by Akt or ERK inhibitor, suggesting that SPNS2 may regulate the malignancy of CRC cells by activating Akt and ERK signalling.…”
Section: Discussionmentioning
confidence: 54%
“…As a confirmation, immunofluorescent staining and IHC showed increased CXCL5 expression in CAFs. In addition, it was demonstrated that nonsmall cell lung cancer, melanoma and CRC tumor cell lines also highly expressed CXCL5 which mold tumor microenvironment . Therefore, it seemed that CXCL5 was with diverse origins.…”
Section: Discussionmentioning
confidence: 73%
“…Our studies suggested that TIMM50 also promoted tumor proliferation and invasion in NSCLC cells via upregulating Cyclin D1 and Snail and downregulating E‐cadherin. During tumor progression, multiple signaling pathways, such as ERK, AKT, P38, and FAK, were involved in modulating the expression of Cyclin D1, Snail, and E‐cadherin . Using Western blotting analysis, we found that overexpression of TIMM50 was capable of upregulating the levels of phosphorylated ERK and P90RSK.…”
Section: Discussionmentioning
confidence: 94%